The ignored performance measure - Volker Laux (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
This paper studies a setting in which a risk averse agent must be motivated to work on two tasks: he (1) evaluates a new project and, if adopted, (2) manages it. While a performance measure which is informative of an agents action is typically valuable because it can be used to improve the risk sharing of the contract, this is not necessarily the case in this two-task setting. I provide a sufficient condition under which a performance measure that is informative of the second task is worthless for contracting despite the agent being risk averse. This shows that information content is a necessary but not a sufficient condition for a performance measure to be valuable.
urn:nbn:de:hebis:30-15245
Keywords: 330; Leistungsbeurteilung; Prinzipal-Agent-Theorie; Anreizvertrag; Theorie